General Election Commission Policy In The Recruitment Process Of Voting Organizing Groups In The 2024 Election - Agus Joko Lelono; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2023)
Elections are clear evidence of a form of democratic system in which the people are involved in determining the direction of the country's political policies for the next five years. Elections are held directly in addition to improving the implementation of the democratic system in the political process. The 2019 election left behind many problems, especially in the case of many KPPS (Polling Organizing Group) officers as election organizers at the TPS level who died. According to a release from the Ministry of Health, as of May 15 2019, 527 2019 election officials had died and 11,239 people were sick. This research aims to analyze the policies implemented by the KPU in the KPPS recruitment process in the 2024 elections. The method used is descriptive analysis with a qualitative approach. The research results show that the KPU as the main election organizing institution which supervises ad hoc officers has made policies based on the principle of clear benefits. The policy formulation process has gone through various processes. From creating issues, advocating issues, to lobbying other policy makers. The KPU's policy in KPPS recruitment has been made in such a way as to accommodate the interests of KPPS as a lower level election organizer. In the policy formation process, the KPU asks for suggestions and recommendations from various parties. Various anticipations have been outlined in the policies produced by the KPU. The author is confident that looking at the pattern of policy formulation used, the KPU will produce policies that are right on target to realize elections with integrity.